2020
DOI: 10.3390/jcm9061689
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Different Types of Exercise Training on Pulmonary Arterial Hypertension: A Systematic Review

Abstract: Pulmonary arterial hypertension (PAH) represents a chronic progressive disease characterized by high blood pressure in the pulmonary arteries leading to right heart failure. The disease has been a focus of medical research for many years due to its worse prognosis and limited treatment options. The aim of this study was to systematically assess the effects of different types of exercise interventions on PAH. Electronic databases were searched until July 2019. MEDLINE database was used as the predominant source… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 113 publications
1
25
0
5
Order By: Relevance
“…Given current research [ 25 ] and the present data, we suggest that patients should be encouraged to remain physically active even in pandemic times, although they should certainly do so in consideration of infection control. Vulnerable populations should also receive therapeutic support to improve their sleep quality and stress management as well as psychological resilience factors.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…Given current research [ 25 ] and the present data, we suggest that patients should be encouraged to remain physically active even in pandemic times, although they should certainly do so in consideration of infection control. Vulnerable populations should also receive therapeutic support to improve their sleep quality and stress management as well as psychological resilience factors.…”
Section: Discussionmentioning
confidence: 76%
“…Here, it has been demonstrated for a large group of participants that lockdown restrictions did not lead to a decrease in sports activity levels in previously low active subjects [ 16 ]. From a therapeutic point of view, this seems to be problematic for PH patients, because a daily activity is an important prognostic factor for the symptomatology and progression of the disease [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, an increasing number of studies have shown the efficacy of exercise training on molecular, functional, physiological, and psychological factors [ 10 , 11 , 12 ]. The first randomized clinical trial for rehabilitation in patients with PAH was reported by Mereles et al in 2006 [ 50 ].…”
Section: The Efficacy and Safety Of Exercise Training In Patients With Pahmentioning
confidence: 99%
“…Exercise training is provided based on an appropriate exercise prescription, which is different from maximal exercise, and it is recognized as an adjunctive therapy for physically deconditioned patients with PAH recently. An increasing number of reports have indicated the efficacy of exercise training in the last decade [ 10 , 11 , 12 ]. Although adverse events could occur during training, only a few serious adverse events have been reported when low-intensity training was closely monitored at a specialized center [ 10 ].…”
Section: Introductionmentioning
confidence: 99%